Forest stakeholders and forestry-based mitigation options: Contributions to low-emission food systems in the Mekong Delta, Vietnam - Pham, T.T.; Nguyen, T.T.A.; Nguyen, T.V.A.; Tran, N.M.H.; Nguyen, T.S.; Nguyen, D.Y.K.; Nguyen, D.T.; Tang, T.K.H. (CIFOR-ICRAF, 2023)
This report was developed based on a literature review of existing laws and policies, and reports on forestry stakeholders, forestry-based mitigation options and their linkages to food systems in the Mekong Delta in Vietnam. The report shows that despite forests playing a vital role in providing food security, this is often overlooked by policymakers and current national and provincial policies. Only a limited number of studies have explored this linkage across the 13 provinces of the Mekong Delta region. This highlights the need for future research to address the knowledge gap to ensure better low-emission food systems in the region. While the Government of Vietnam has acknowledged the important roles forests play in its Nationally Determined Contribution (NDC), and has developed forestry-based mitigation options, the area of forest in the Mekong Delta region has fallen over the last 20 years. Although forestry-based mitigation options are now being supported and co-funded by a wide range of actors, including forest owners, government agencies, international organizations, donors and private sector parties, their outcomes have been ineffective due to unclear tenure, conflicts of interest and weak coordination between different actors. Most Mekong Delta provinces have developed plans to address these challenges, but doing so will require macro policy changes and political commitment to protect mangroves, which do not always fall within the sphere of influence of provincial governments. Forestry-based mitigation options have direct impacts on the earnings and food consumption of the poor, women and Indigenous Peoples in the Mekong Delta. However, these vulnerable groups are rarely involved in decision making over policies and practices. They also have difficulties participating in and benefitting from government, international, private and public-private partnership programmes as they are landless or live on contested areas of land. Ensuring forestry-based mitigation options can contribute to low-emission food systems but will require cross-sectoral approaches, participatory decision-making processes and evidence-based analyses for determining viable options. Social inclusion and social safeguards will be essential for ensuring forestry-based mitigation and future low-emission food systems leave no one behind and do not result in social marginalization of vulnerable groups.